2016
DOI: 10.1097/ccm.0000000000001666
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Novel Risk Prediction Scores for Community-Acquired Sepsis and Severe Sepsis*

Abstract: Objective We sought to derive and internally validate a Sepsis Risk Score (SRS) and a Severe Sepsis Risk Score (SSRS) predicting long-term risks of future sepsis and severe sepsis events among community-dwelling adults. Design National population-based cohort. Setting United States. Subjects 30,239 community-dwelling adults ≥45 years old in the national REasons for Geographic and Racial Differences in Stroke (REGARDS) cohort. Interventions None. Measurements and Main Results Over a median of 6.6 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…Societal rates of MI, stroke, or cardiovascular disease mortality have been mitigated by organized prevention efforts [ 39 ]. In prior studies we have identified a host of novel risk factors associated with sepsis susceptibility [ 40 ]. Additional study must identify other potential interventions to limit and reduce long-term rates of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Societal rates of MI, stroke, or cardiovascular disease mortality have been mitigated by organized prevention efforts [ 39 ]. In prior studies we have identified a host of novel risk factors associated with sepsis susceptibility [ 40 ]. Additional study must identify other potential interventions to limit and reduce long-term rates of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Medical conditions included atrial fibrillation, chronic kidney disease (CKD), diabetes, dyslipidemia, hypertension, lung disease, myocardial infarction (MI), obesity, and stroke [22,23]. Using baseline characteristics, we calculated a Sepsis Risk Score for each participant [24]. Year of hospitalization and age at the time of hospitalization were also determined.…”
Section: Participant Baseline Characteristicsmentioning
confidence: 99%
“…Выбор инфузи-онной среды -все, в чем можно плавать! Факторы риска в шкалах Sepsis Risk Score и Severe Sepsis Risk Score (H. Wang et al, 2016): возраст более 75 лет, белая раса, табакокурение, хроническое за-болевание легких, заболевания периферических ар-терий, диабет, инсульт, фибрилляция предсердий, ишемическая болезнь сердца (ИБС), ожирение, ги-пертензия, тромбоз глубоких вен, мужской пол, СРБ > 3 мг/дл, цистатин С  11 мг/дл, клубочковая филь-трация < 60 мл/мин/1,73 м 2 . Трактовка факторов риска в шкалах Sepsis Risk Score и Severe Sepsis Risk Score: низкий риск -0-3 пунктов, средний риск -7-9 пунктов, высокий риск -10-12 пунктов [6].…”
unclassified